Review on structural properties metrics in SOA design - Nik Daud, Nik Marsyahariani (Penerbit UTM Press, 2015)
The application of metrics for the purpose of measuring qualities of software has been widely practice within software engineering industry. Though in the beginning most measurement involves artifacts such as source code, quality measurement from the beginning of software lifecycle is slowly gathering attention. Service-Oriented Architecture (SOA) is a new paradigm that introduces way to develop software in a faster way by adopting available services. SOA application is better comprehended using its composition design. Thus in earlier researches, many metrics had been proposed in relation to SOA design. This paper focuses on proposed metrics from earlier research works specifically one that measure the structural properties of SOA application. The structural properties metrics selected are analyzed from both static and dynamic perspectives. Around seventeen papers are selected during the data collection process. The proposed metrics are then separated into its respective properties type and are further analyzed to find required characteristics for each discussed property. The result from the analysis is list of construction characteristics for each structural property that can be used as guidelines for future researchers that incline on proposing new metrics. The metrics classification also indicates on research gap within the area of structural properties metrics in SOA domain.